Japanese space policy: An international legal perspective - A. N. Vylegzhanin; M. R. Yuzbashyan; M. E. Muntian (Японские исследования)
Japan’s advancements in technology and its strategic focus on space policy have driven swift advancements in the field, attributed to Japan’s ability to balance scientific exploration, industrial growth, and national defense. This article examines Japan’s national legal framework governing space activities. The key pieces of legislation analyzed are the Law Concerning Japan Aerospace Exploration Agency of 2002, the Basic Space Law of 2008, the Act on Launching of Spacecraft, etc. and Control of Spacecraft of 2016, the Act on Ensuring Appropriate Handling of Satellite Remote Sensing Data of 2016, and the Act on the Promotion of Business Activities for the Exploration and Development of Space Resources of 2021. The analysis of these activities is conducted in accordance with the relevant international space legal framework. The article delves into the shift in Japan’s space policy from “non-military” to “non-aggressive” in 2008 and its impact on national legislation. An examination is provided of the fourth law in the world (following similar actions by the USA, Luxembourg, and the UAE) concerning the exploitation of natural resources of celestial bodies, enabling private entities to conduct exploration and extraction activities. This is especially noteworthy given the lack of direct international legal oversight on space resource utilization. This article also examines Japan’s international legal space policy, including the Japan-U.S. Framework Agreement on Cooperation in the Exploration and Peaceful Uses of Outer Space, including the Moon and Other Celestial Bodies 2023, in light of the particularly close Japan-U.S. cooperation in space exploration and use. Japan’s enactment of a law regarding the exploration and exploitation of natural resources of celestial bodies, along with Japan’s participation in projects such as Artemis, Lunar Gateway, and Hakuto-R, demonstrates its growing role in international space projects and its pursuit of the closest possible cooperation with the United States in ensuring national security through the use of outer space. The conclusion offers summarizing statements.